Impact of Guided Imagery on Depression, Stress and Anxiety among Wives of Patients with Alcohol Use Disorder (International Journal of Nursing Education, 2021)
The purpose of this article is to evaluate the impact of Guided Imagery (GI) on Depression, Stress andAnxiety among wives of patients with Alcohol Use Disorder (AUD). Many studies have examined theprotective factors associated with individual’s mental illness. In some studies, consumption of Alcohol hadan inverse relationship to mental health problems, whereas in other studies, it leads to serious effects on thefamily members of the AUD patients. If not properly managed, stress can lead to disturbances in cognitivefunctioning, mood-related problems, obesity, and heart disease. Guided imagery has been shown to be aneffective technique to help people recover from stress. The literature on guided imagery, however, doesnot take the theme of the guided imagery script into account. Additionally, there are gaps in the researchregarding any interaction between rurality and mood, stress, and guided imagery. Guided Imagery describestechniques that use visualizations and draw on the participants’ active imagination and mental imagery.It typically involves a person directing the mental exercises and the participants are guided throughsuggestions to evoke specific images. It is used as psychotherapy, as a relaxation or meditation technique,or experimentally to evoke specific emotional states.Guided Imagery is cost effective, noninvasive, nonpharmacologicalcomplementary and alternative therapy to reduce the level of depression, stress and anxietyamong wives of AUD patients.